2022
DOI: 10.3390/nano12030490
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Supercapacitor Performance of a Mixed-Phase Mn-Doped MoS2 Nanoflower

Abstract: The fascinating features of 2D nanomaterials for various applications have prompted increasing research into single and few-layer metal dichalcogenides nanosheets using improved nanofabrication and characterization techniques. MoS2 has recently been intensively examined among layered metal dichalcogenides and other diverse transition metal-based materials, that have previously been studied in various applications. In this research, we report mixed-phase Mn-doped MoS2 nanoflowers for supercapacitor performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…From the Ragone plot in Figure 4 g, the 0.3Mn-Co 3 O 4 /AC//ASC achieves a maximum energy density of 43.5 W h/kg, at a power density of 1350 W/kg. The corresponding energy and power densities of these supercapacitors are shown in Table 2 [ 21 , 35 , 36 , 37 , 38 ]. To explore the cycling stability of the device, 10,000 charge and discharge tests were carried out.…”
Section: Resultsmentioning
confidence: 99%
“…From the Ragone plot in Figure 4 g, the 0.3Mn-Co 3 O 4 /AC//ASC achieves a maximum energy density of 43.5 W h/kg, at a power density of 1350 W/kg. The corresponding energy and power densities of these supercapacitors are shown in Table 2 [ 21 , 35 , 36 , 37 , 38 ]. To explore the cycling stability of the device, 10,000 charge and discharge tests were carried out.…”
Section: Resultsmentioning
confidence: 99%
“…Among the transition metal sulfides, MoS 2 is a promising electrode material for supercapacitor applications, because of its fascinating sheet-like structure, which provides a huge surface area for double-layered charge storage and a greater intrinsic fast ionic conductivity. [15][16][17] MoS 2 is made up of covalently S-Mo-S atoms held together by weak van der Waals interactions and has a theoretically larger capacity than graphite. It comes in a variety of polytype formations, including 2H and 1 T phases, as well as oxidation states ranging from +2 to +6.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their natural abundance, easily controllable morphologies, multiple valences, and acceptable bandgap widths, various transition metal sulfides, including that of copper sulfide, nickel sulfide, zinc sulfide, molybdenum sulfide (MoS 2 ), manganese sulfide, strontium sulfide, and vanadium sulfide, have stirred interest for supercapacitor applications. Among the transition metal sulfides, MoS 2 is a promising electrode material for supercapacitor applications, because of its fascinating sheet‐like structure, which provides a huge surface area for double‐layered charge storage and a greater intrinsic fast ionic conductivity 15‐17 . MoS 2 is made up of covalently S‐Mo‐S atoms held together by weak van der Waals interactions and has a theoretically larger capacity than graphite.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Vikraman et al engineered the active sites of MoS 2 by transition metal doping using a conventional chemical precipitation technique and they concluded that metal-doped MoS 2 is a process with a high specific capacitance of 353 F g −1 with a high capacitance retention rate of 94% [9]. Bello et al reported the charge storage performance of the Mn-doped MoS 2 nanoflowers, they noticed that metal doping can effectively enhance the energy storage performance of the 2D MoS 2 [17]. Likewise, Raj et al investigated the effect of energy storage performance of VSe 2 before and after the cobalt insertion and they found capacitance enhancement after the addition of Co due to the synergy interplay between the heteroatom and the TMTD.…”
Section: Introductionmentioning
confidence: 99%